Sir Cumference and the roundabout battle : a math adventure - Neuschwander, Cindy; Geehan, Wayne (Watertown, MA : Charlesbridge, 2015)
"When Steward Edmund Rounds and Sir Cumference notice that there are strangers camped nearby, Rounds II decides to investigate despite being involved with the task of learning how to make accurate counts of the castle's stores of food, supplies, and weaponry. When he reports back that an enemy is lying in wait, everyone moves quickly to defend the castle ... Using rounding techniques to figure out the totals more quickly, Rounds II is just in time to help stave off a potentially disastrous attack"--Publisher.
School Library Journal
School Library Journal, August 2015
3-6
Keywords: Counting -- Juvenile literature; Rounding (Numerical analysis) -- Juvenile literature; Counting; Rounding (Numerical analysis); Counting; Numerical analysis